Impact of body mass index on outcome and health status after chronic total occlusion percutaneous coronary intervention: Insights from the OPEN‐CTO study. Issue 6 (22nd April 2020) - Patterson, Christian; Sapontis, James; Nicholson, William J.; Lombardi, William; Karmpaliotis, Dimitri; Moses, Jeffrey; Gosch, Kensey L.; Grantham, J. Aaron; Hirai, Taishi; ,
Abstract: Background: The effect of body mass index (BMI) on the procedural outcomes and health status (HS) change after chronic total occlusion (CTO) percutaneous coronary intervention (PCI) is largely unknown. Methods: Thousand consecutive patients enrolled in a 12‐center prospective CTO PCI study (Outcomes, Patient Health Status, and Efficiency in Chronic Total Occlusion Hybrid Procedures [OPEN‐CTO]) were categorized into three groups by baseline BMI (obese ≥30, overweight 25–30, and normal 18.5–25), after excluding seven patients with BMI <18.5. Baseline and follow‐up HS at 1 year were quantified using the Seattle Angina Questionnaire, Rose Dyspnea Score, and Personal Health Questionnaire‐8 (PHQ‐8). Hierarchical, multivariable logistic, and repeated measures linear regression models were used to assess procedural success, major adverse cardiovascular and cerebrovascular events (MACCE), and HS outcomes, as appropriate. Results: The obese and overweight were 47.6% and 37.4%, respectively. While procedure time and contrast dose were similar among the groups, total radiation dose (mGy) was higher with increased BMI (3, 019 ± 2, 027, 2, 267 ± 1, 714, 1, 642 ± 1, 223, p  < .01). Procedural success rates, as well as MACCE rates, were similar among the three groups (obese 83.1%, overweight 79.8%, normal 81.9%, p  = .47 and 5.1, 8.4, and 8.7%, p  = .11). These rates remained similar after adjustment for baseline characteristics. The HS improvement from baseline to 12 months after adjustment was similar in obese and overweight patients compared to normal weight patients. Conclusions: CTO PCI in obese and overweight patients can be performed with similar success and complication rates. Obese and overweight patients derive similar HS benefit from CTO PCI compared to normal weight patients.